The economic burden of environmental tobacco smoke in the first year of life. Issue 9 (22nd August 2003) - Leung, G M; Ho, L-M; Lam, T-H
Abstract : Aims: To examine the population impact and economic costs associated with environmental tobacco smoke (ETS) in Chinese infants with non-smoking mothers. Methods: Prospective, population based birth cohort study in Hong Kong, 1997–98. Main outcome measures were: doctor consultations and hospitalisations; adjusted odds ratios for higher utilisation by service type for each of the ETS exposure variables; corresponding population attributable risks (PARs); and associated extra health care costs. Results: For the 1997 annual birth cohort, ETS exposure through the mother in utero was positively associated with higher consultation (adjusted odds ratio (OR) 1.26) and hospitalisation (OR 1.18) due to any illness. This translated into 7.4% of all inpatient episodes in the first year of life, representing an additional 1581 hospital attendances that cost over US$2.1 million. The corresponding PAR for outpatient services was 7.7%, where the majority was due to respiratory or febrile illnesses, accounting for $0.44 million in extra costs. Postnatal exposure to ETS at home was linked to higher rates of hospitalisations for any illness compared with non-exposed infants (OR 1.12), which led to 662 extra hospitalisations consuming $0.90 million, where the associated PAR was 3.1%. Conclusions: Assuming that ETS was causally associated with health services use, about 9% of the total direct medical costs in the first year of life can be attributed to passive smoking. The community, as well as the private citizen, needs to be made aware of the costs foregone from exposure to tobacco smoke as well as the potential savings from a smoke-free society.